2021
DOI: 10.1002/aqc.3539
|View full text |Cite
|
Sign up to set email alerts
|

Detection of protection benefits for predatory fishes depends on census methodology

Abstract: 1. Marine protected areas (MPAs) are used as fisheries management and conservation tools. Well-enforced no-take zones allow the rebuilding of natural populations of exploited species; however, there is still controversy on the role of buffer zones.2. The effectiveness of MPAs could be underestimated, as fish population assessments depend largely on traditional methodologies that have difficulties in detecting predatory fish because of their low abundances, their patchy distribution, and their reaction to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Different colours indicate different individuals, which are listed in ascending order of number of sightings from top to bottom et al 2018). Recent studies reported high spatio-temporal variability in the number of medium-to-large sized fish species occurring at low densities and characterised by patchy distributions, such as groupers (Irigoyen et al 2018;Rojo et al 2021). Variability in abundance estimates can be reduced, theoretically, by increasing the census area and/or by increasing the number of replicates (Underwood 1997;Kulbicki and Sarramégna 1999;Prato et al 2017;Irigoyen et al 2018;Rojo et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different colours indicate different individuals, which are listed in ascending order of number of sightings from top to bottom et al 2018). Recent studies reported high spatio-temporal variability in the number of medium-to-large sized fish species occurring at low densities and characterised by patchy distributions, such as groupers (Irigoyen et al 2018;Rojo et al 2021). Variability in abundance estimates can be reduced, theoretically, by increasing the census area and/or by increasing the number of replicates (Underwood 1997;Kulbicki and Sarramégna 1999;Prato et al 2017;Irigoyen et al 2018;Rojo et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported high spatio-temporal variability in the number of medium-to-large sized fish species occurring at low densities and characterised by patchy distributions, such as groupers (Irigoyen et al 2018;Rojo et al 2021). Variability in abundance estimates can be reduced, theoretically, by increasing the census area and/or by increasing the number of replicates (Underwood 1997;Kulbicki and Sarramégna 1999;Prato et al 2017;Irigoyen et al 2018;Rojo et al 2021). In our study, we used widely employed 25 × 5 m 2 strip transects due to i) the limited spatial extension of the area surveyed at each study site (especially Secche Papa) and ii) the need for an acceptable number of replicated counts to estimate variability (i.e., n = 4 per dive and study site).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cabo de Palos -Islas Hormigas marine reserve (hereafter CPMR) is considered one of the most ecologically effective MPAs in the whole of the Mediterranean Sea (García-Charton et al, 2004;Rojo et al, 2021a;Rojo et al, 2021b), hosting a disproportionally high biomass of the rocky reef fish assemblage compared to other effective Mediterranean MPAs, encompassing high densities of large-size predators around the rocky shoals and small islets characterising the reserve (Rojo et al, 2021a;Rojo et al, 2021b). For this reason, the area is considered one of the most attractive Mediterranean diving destinations, and as a result the number of diving charter businesses operating in the area increased from 1 to 9 since the establishment of the MPA, and the number of divers visiting the MPA each year increased from about 8,000 in 1998 to more than 32,000 in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being one of the main components of biodiversity, fish fauna also play an important role in both the ecological processes of marine ecosystems (Guidetti, 2006) and the economic activities of coastal communities, such as fisheries and sea-related tourism (e.g., diving, snorkeling and excursions; Harasti et al, 2015). Therefore, accurate, rapid, and cost-effective fish assemblage monitoring is a pivotal tool for MPA management (Baker et al, 2016), to verify whether and to what extent the MPA conservation objectives have been achieved, thus evaluating the reserve effectiveness, and redefining these objectives in the framework of the adaptive management (Rojo et al, 2021). In fact, an inadequate assessment of the state of fish assemblages can lead to an increase in exploitation quotas, in the case of excessive estimates of their abundance, or to an unnecessary tightening of restrictions on human activities, in the event of underestimation (Ward-Paige et al, 2020).…”
Section: Introductionmentioning
confidence: 99%